2016
DOI: 10.2146/ajhp150677
|View full text |Cite
|
Sign up to set email alerts
|

Stability of tacrolimus injection diluted in 0.9% sodium chloride injection and stored in Excel bags

Abstract: Extemporaneously prepared infusion solutions of tacrolimus 2, 4, and 8 μg/mL in 0.9% sodium chloride injection in Excel bags were chemically and physically stable for at least nine days when stored at room temperature (23 °C) without protection from light and when stored in a refrigerator (4 °C) in the dark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Following acquisition of our novel stability data, the pilot phase was then instituted from 1 April 2015 to 30 June 2015, during which patients received tacrolimus IV standard concentration (Figure 2). 7 Patients were included if they received IV tacrolimus on the pilot unit during the study inclusion period. Patients were no longer followed after the patient was switched to oral tacrolimus or transferred off the pilot units (i.e., ICU or other unit).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following acquisition of our novel stability data, the pilot phase was then instituted from 1 April 2015 to 30 June 2015, during which patients received tacrolimus IV standard concentration (Figure 2). 7 Patients were included if they received IV tacrolimus on the pilot unit during the study inclusion period. Patients were no longer followed after the patient was switched to oral tacrolimus or transferred off the pilot units (i.e., ICU or other unit).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous physico-chemical stability studies showed that tacrolimus admixtures prepared in NS in Excel® bags (B. Braun Medical Inc., Bethlehem, PA), at concentrations of 2, 4, and 8 µg/mL, were chemically and physically stable for at least 9 days when stored at room temperature (23℃) without protection from light, and at least 9 days when stored in the refrigerator (4℃) in the dark. 7 Thus, the beyond use date (BUD) of tacrolimus IV standard concentration was 9 days under refrigeration. 7,9 The BUD was not implemented until 1 May 2015 after the stability study results were available and batching began.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of compatible stability of chemical medicine injections and infusion solutions have been reported in many studies ( Binnor et al, 2013 ; Chen et al, 2015a , b ; Myers et al, 2016 ). As chemical medicine injections generally contain only single active component, the change of single active component can represent the change of injection stability.…”
Section: Introductionmentioning
confidence: 99%